A prognostic pyroptosis-related LncRNA classifier associated with the immune landscape and therapy efficacy in glioma - Zhong, Jiasheng; Liu, Jie; Huang, Zhilin; Zheng, Yaofeng; Chen, Jiawen; Ji, Jingsen; Chen, Taoliang; Ke, Yiquan (Frontiers in Genetics, 2022)
Recent studies have found that long noncoding RNAs (lncRNAs) play an important role in the regulation of tumor pyroptosis. However, the prognostic value of pyroptosis related lncRNAs has not been thoroughly explored. In this study, the transcriptome and somatic mutation data and clinical information were all downloaded from TCGA and CGGA. We identified 11 prognostic pyroptosis related lncRNAs to construct a pyroptosis-related lncRNAs classifier through the correlation analyses-boruta algorithm-lasso regression-multivariate Cox regression analysis. We verified the predictive performance of the classifier on the training set (TCGA, CGGA_693) and validation set (CGGA_325), revealing a poorer survival outcome for patients in the high-risk group and a better prediction performance than other clinical features. Then a nomogram with improved accuracy for predicting overall survival (OS) was established based on prognostic factors in the univariate cox regression analysis. Moreover, the difference in the microenvironment between the high- and low- risk groups was evaluated by the CIBERSORT algorithm, the ESTIMATE algorithm, expression of the immune check point, and mutation profile. Finally, we compared the efficacy of radiotherapy and predicted the response to chemotherapy and immunotherapy between the high- and low- risk groups, suggesting that patients with GBM or older than 50 years old in the high-risk group had a better survival outcome from radiotherapy, and that patients from different risk stratifications respond differently to chemotherapy and immunotherapy. In conclusion, we identified the prognostic pyroptosis-related lncRNAs in glioma and constructed a prognostic classifier that was associated with the immune landscape of the glioma microenvironment and may guide treatment.